Factors Affecting Diagnostic Delay of Advance HIV Disease at Enrolment in the Indus Hospital, Karachi Pakistan - Muqtadir, Jamil; Sarfaraz, Samreen; Salahuddin, Naseem (Infectious Diseases Journal of Pakistan, 2022)
Background: Human immunodeficiency virus (HIV) infection is characterized by decreased CD4 cell count leading to opportunistic infections (OIs) and tumors. We have evaluated clinical profile, frequency and factors affecting the diagnostic delay of patients presenting with advanced HIV in Indus Hospital Karachi. There are limited studies in Pakistan which has evaluated risk factors for acquiring HIV infection therefore, this study was conducted. Methods: A retrospective study was done at the Indus Hospital Karachi, from January to December 2017. All patients presenting with advanced HIV were included in the study. Clinical profile, frequency and factors affecting the diagnostic delay were evaluated. Results: During study period 248, HIV patients were registered, of which 56(23%) had advanced HIV. Out of 56 patients, one was excluded due to Chronic Liver Disease. 45(82%) were male, 8(15%) were female and 2(4%) were transgender. Weight loss was the commonest symptom, followed by fever and loose stools. All patients had been visiting multiple health-care professionals before their final diagnosis was made. Among risk factors, exposure to female sex workers (34.9%) found to be commonest risk factor followed by injection drug use. Among the factors responsible for diagnostic delay, 94.5 % was missed diagnosis from health-care professionals, followed by lack of awareness from patients. Pallor was the commonest clinical examination finding, followed by oral thrush and lymphadenopathy. Hepatitis C was the most common coinfection, followed by syphilis and hepatitis B. Candidiasis was the most common opportunistic infection (27%), seven had oral candidiasis, seven had esophageal candidiasis and one had extensive gastrointestinal candidiasis. PCP (Pneumocystis carinii pneumonia) was the second most common opportunistic infection present in eleven 20%, followed by CMV (Cytomegalovirus) infection, MAC (Mycobacterium avium complex) colitis, cryptococcal meningitis and toxoplasmosis. Thirteen (23.2%) patients had other infections. 31 patients were followed, 12 were lost to follow-up, 8 died; 5 of PCP (Pneumocystis carinii pneumonia), 1 of cryptococcal meningitis, 2 of unknown cause while 4 were transferred to other facilities. Conclusion: Advanced HIV represent about one third of all HIV patients. Weight loss was the commonest feature followed by fever and loose stools. Exposure to female sex workers was commonest risk factor for acquiring infection. Missed diagnosis was the commonest factor affecting the diagnostic delay. Key words: Human immunodeficiency virus, Opportunistic infections, Pneumocystis carinii pneumonia, Cytomegalovirus, Mycobacterium avium complex.